Pengaruh Kepemimpinan, Kecerdasan Emosional dan Kompetensi Terhadap Kinerja Karyawan - Hafidz Naufal Garnita (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
This research was conducted based on the phenomenon that occurred that the Badan Pengelolaan Pendapatan Daerah (BPPD) of Bandung City was still not maximal in implementing leadership, emotional intelligence and competencies that could affect employee performance. The research method used in this research is descriptive and verification research methods with a total sample of 66 respondents. Testing research instruments using validity and reliability tests. The data analysis method used is path analysis, multiple correlation and the coefficient of determination. The results of this study indicate that there is a positive and significant influence between leadership, emotional intelligence and competence on employee performance of the employees of Badan Pengelolaan Pendapatan Daerah (BPPD) either simultaneously or partially. Based on the analysis of the coefficient of determination simultaneously leadership, emotional intelligence and competence have a positive and significant effect on employee performance by 86.8%. Partially, leadership has an effect on performance by 25.23%, emotional intelligence on performance is 26.82% and competence on employee performance is 34.73%.